2021
DOI: 10.1038/s41598-021-00763-z
|View full text |Cite
|
Sign up to set email alerts
|

Auto/paracrine factors and early Wnt inhibition promote cardiomyocyte differentiation from human induced pluripotent stem cells at initial low cell density

Abstract: Cardiomyocytes derived from human induced pluripotent stem cells (hiPSCs) have received increasing attention for their clinical use. Many protocols induce cardiomyocytes at an initial high cell density (confluence) to utilize cell density effects as hidden factors for cardiomyocyte differentiation. Previously, we established a protocol to induce hiPSC differentiation into cardiomyocytes using a defined culture medium and an initial low cell density (1% confluence) to minimize the hidden factors. Here, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Several studies reported that Wnt and Smad signaling pathways play an important role in the fate determination of stem cells and their potential for cardiovascular differentiation. Several studies reported that early application of Wnt/β-catenin signaling pathway inhibitor, IWR1 promotes cardiomyocyte differentiation[ 12 ]. Similarly, IWP-4 is a potent small molecule that has been reported to differentiate embryonic stem cells into cardiomyocyte like cells[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that Wnt and Smad signaling pathways play an important role in the fate determination of stem cells and their potential for cardiovascular differentiation. Several studies reported that early application of Wnt/β-catenin signaling pathway inhibitor, IWR1 promotes cardiomyocyte differentiation[ 12 ]. Similarly, IWP-4 is a potent small molecule that has been reported to differentiate embryonic stem cells into cardiomyocyte like cells[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CD49f is a marker of stem/progenitor cell populations [ 37 ], including cardiac stem cells, and was expressed here only in PRRX1 low Day 4 cells. High cell density inhibits WNT signaling to promote cardiomyocyte differentiation from hiPSCs [ 38 ] and the expression level of PRRX1 in cardiac mesoderm is lower than that of forelimb mesoderm [ 18 , 39 ], indicating that high cell density may have promoted the cardiac mesoderm-directed differentiation of LPM cells.…”
Section: Discussionmentioning
confidence: 99%
“…This allows us to replace dysfunctional cardiomyocytes and build cardiovascular disease models for drug screening and also cardiotoxicity testing. [6][7][8] However, the predictive powers of these models are limited by the immature state of the ECTs. Many studies have been conducted to improve the maturity of hiPSC-CMs and ECTs to overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%